Pengembangan Jobsheet Trainer Motor Listrik di Sekolah Menengah Kejuruan - Romi Fadli; Muldi Yuhendri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
One of the practical subjects in the Electrical Power Installation Engineering department of SMK Negeri 2 Sawahlunto is the installation of an electric motor. One of the factors that support the smooth implementation of the practicum is the availability of a jobsheet as a guide in practice. In this study, a jobsheet was developed to obtain a valid and practical jobsheet in the subject of Electrical Motor Installation. Jobsheet development is carried out based on the 4D development research method, which includes defining, designing, developing and disseminating stages. The validity of the jobsheets is evaluated through media and material experts, while the practicality of the jobsheets is evaluated through users. The validity and practicality of the jobsheets were tested using a questionnaire. The results showed that the jobsheets developed for electrical motor installation subjects were feasible to use. This can be seen from the results of practicality tests and validity tests that have been carried out. The results of the validity test of the three validators obtained an average score of 90% in the valid category, while the results of the Practicality test from the teacher obtained a score of 84% in the very practical category, and the practicality test of students obtained an average score of 86% with a very practical category.